2016
DOI: 10.1080/19443994.2016.1159992
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pathogen disinfection and regrowth in a simple graywater recycling system for toilet flushing

Abstract: A B S T R A C TGraywater treatment systems must inactivate pathogens, prevent regrowth, be low cost, and be simple to operate to support their widespread adoption for alleviating water stress. A treatment system comprised only of filtration and disinfection could meet these constraints. To investigate pathogen disinfection and regrowth in such a system with minimal organic matter removal, herein three disinfectants (chlorine, ultraviolet irradiation, and ozone) were tested in combination with three filter type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In contrast, Ekeren et al (2016), who specifically tested high organic waters (Turbidity 26-37 NTU), found full inactivation of E. coli and S. enterica at CTs of 180-474 mg/L-min. Although they applied greater CTs, Ekeren et al (2016) attributed the observed disinfection efficiency to a phenomenon observed by others (Dietrich et al, 2003;Winward et al, 2008b) in which water with greater organic content allows for greater initial chlorine dosages while not exceeding residual limits (a residual greater than 4 mg/L will damage metal fixtures), and greater initial chlorine dosages increase chlorine particle penetration to inactivate particleassociated microorganisms.…”
Section: Chlorine Disinfection Trialsmentioning
confidence: 90%
See 4 more Smart Citations
“…In contrast, Ekeren et al (2016), who specifically tested high organic waters (Turbidity 26-37 NTU), found full inactivation of E. coli and S. enterica at CTs of 180-474 mg/L-min. Although they applied greater CTs, Ekeren et al (2016) attributed the observed disinfection efficiency to a phenomenon observed by others (Dietrich et al, 2003;Winward et al, 2008b) in which water with greater organic content allows for greater initial chlorine dosages while not exceeding residual limits (a residual greater than 4 mg/L will damage metal fixtures), and greater initial chlorine dosages increase chlorine particle penetration to inactivate particleassociated microorganisms.…”
Section: Chlorine Disinfection Trialsmentioning
confidence: 90%
“…If we exclude the trials from Ekeren et al (2016), which intentionally tested water of high organic carbon content, all disinfection trials treated water with turbidity values less than 10 NTU. If we compare these trials to the effluent produced by wetlands in Table 3, we see that not all wetlands were able to produce water with these low turbidity values.…”
Section: Greywater Disinfection Processesmentioning
confidence: 99%
See 3 more Smart Citations